Implementasi Agile Scrum Pembuatan Game Visual Novel Cerita Asal Usul Kota Surabaya - Artiarini Kusuma Nurindiyani; Ashafidz Fauzan Dianta; Halimatus Sa’dyah; Ilham Agung Riyadi (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2023)
Surabaya is the second largest city in Indonesia after Jakarta. The city of Surabaya has a distinctive designation, namely "the city of heroes" because of the great support from the people of Surabaya in fighting for Indonesian independence. The lack of interest of Indonesia's younger generation in Indonesian folklore and their preference for video games and other advanced technology, does not rule out the possibility that history will be forgotten and slowly extinct because it is only passed down orally. The purpose of this research is to implement the agile-scrum method in making visual novel games as an effort to attract the interest of the younger generation to know and preserve the history of the origins of the city of Surabaya with a modern approach and according to the target audience. The visual elements used in this game are costume details, props, poses and various expressions according to modified references. In addition, the narration/storyline used has also been developed with a story style and choice of words that are relevant to the target user. The method used in this final project is agile-scrum which has 8 stages of development, starting from the stage of exploring problems that can become product ideas to the final testing stage. From the results of the final test, the creation of a visual novel game based on the story of the origins of the city of Surabaya can be used properly by users.